Bio-Inspired Silicon-Based Materials - Zelisko, Paul M. (Advances in Silicon Science, 2014)
The contributed volume addresses a wide range of topics including, but not limited to, biotechnology, synthetic chemistry, polymer chemistry and materials chemistry. The book will serve as a specialized review of the field of biologically inspired silicon-based structures. Researchers studying biologically inspired silicon materials chemistry will find this volume invaluable.